THE EFFECT OF HYALURONIC ACID COMPOUNDS IN THE COMPLEX TREATMENT OF GENERALISED PERIODONTITIS: A SYSTEMATIC REVIEW OF SCIENTIFIC LITERATURE (Ustozlar uchun, 2026)
Gingivitis and periodontitis, together referred to as periodontal disorders, are chronic infections of the periodontal tissues linked to biofilms (1,3). Globally, 20 to 50 percent of individuals are afflicted by periodontal diseases, with severe periodontitis being a primary contributor to tooth loss. Surgical and conservative methods are used to treat gingivitis and periodontitis (5,6).A considerable array of adjuvant drugs has been suggested to enhance the clinical trajectory after primary therapy, used alongside primary therapeutic strategies (7). These adjuvants include diverse anti-inflammatory, antibacterial, and antiseptic agents, including chlorhexidine and essential oils. Additional chemicals that facilitate tissue regeneration and healing include hyaluronic acid (HA) and enamel matrix proteins.